Designing Materials for Teaching Arabic to Speakers of Other Languages/تصميم مواد تعليم اللغة العربية للناطقين بلغات أخرى - Salih Jamaan Al Zahrani; Ismaya Ismaya (UIN ANTASARI, 2021)
The student of Darul Hijrah Boarding School and students of Bina Islam boarding school in teaching of Arabic book curriculum 2013 in level high school are not relevan for them, they get easy in teaching it and material literature is not interisting fotr them, and beside that have to looking for the other book in teaching Arabic language.Based on the problems above, the writer to try to design of the book from the literature of Arabic, it is not was studying in the school in the hope can to help the students equipment the knowlagde of the materials literaure.The result of the research they are: 1) the product of teaching materials about literature Arabic for the student level high school of Islamic boarding.This research used qualitative and quantitative approach and the type of this research was a kind of “Research and Development” ( R & D ).Need to be proposed in research are: 1) the totur should design teaching materials more interesting and adding insight of the students, 2) the materials of the Arabic literature are adding insigh and to complement the book for understanding literature Arabic was not taught again in the boarding.